Robust adaptive prescribed performance control for dynamic positioning of ships under unknown disturbances and input constraints - Li, Jian; Du, Jialu; Hu, Xin (Ocean engineering, 2020)
A robust adaptive prescribed performance control (RAPPC) law is proposed for dynamic positioning (DP) of ships subject to unknown time-varying disturbances with the control input magnitude and rate constraints. A simple error mapping function is first constructed to achieve the DP prescribed performance control design. Next, an adaptive disturbance observer is proposed to online estimate the unknown time-varying disturbances and an auxiliary dynamic system is introduced to addresses the effects of the input magnitude and rate constraints. Then, incorporating the above into the dynamic surface control method, the DP control law with prescribed performance is proposed. Theoretical analysis and simulation results prove that the proposed DP RAPPC law makes the ship's position and heading be maintained at the desired values with prescribed positioning performance. •This paper for the first time develops the prescribed performance control law for dynamic positioning (DP) of ships subject to unknown time-varying disturbances under the control input magnitude and rate constraints.•A simple error mapping function is proposed to achieve the DP prescribed performance control design.•An adaptive disturbance observer is developed to provide online estimates of the unknown time-varying disturbances, as a result, the robust DP of ships is conveniently realized through adaptive control algorithms and has less conservativeness.•An auxiliary dynamic system is constructed to mitigate the effect of the input magnitude and rate constraints.